Experimental evaluation and structure–activity relationship analysis of bridged-ring terpenoid derivatives as novel Blattella germanica repellent. Issue 12 (2nd December 2022) - Wang, J.; Si, H.; Liu, Y.; Song, J.; Wang, P.; Luo, H.; Chen, S.; Fan, G.; Rao, X.; Wang, Z.; Liao, S.
ABSTRACT: Cockroaches are urban pests that are very difficult to control. Using repellents is a green, safe and effective strategy for their control. In order to find novel cockroach repellents, the repellent activity of 45 bridged-ring terpenoid derivatives synthesized from β-pinene against Blattella germanica was tested. The relationship between the molecular structure of these bridged-ring terpenoid derivatives and their repellent activity against Blattella germanica was also analysed. The results show that some of the bridged-ring terpenoid derivatives exhibit good repellent activity against Blattella germanica, and six compounds (RR = 60.44–87.32%) show higher repellent activity against Blattella germanica than DEET (RR = 54.77%), making them promising for development as new cockroach repellents. Quantitative structure–activity relationship (QSAR) analysis revealed that the HOMO-1 energy, Kier and Hall index (order 2), Balaban index, and relative positive charged surface area of bridged-ring terpenoid derivatives have effects on repellent activity against Blattella germanica . The present study may provide a theoretical basis for the high-value use of β-pinene and can be helpful to the development of novel repellents against Blattella germanica .